2016
DOI: 10.1038/srep32843
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide profiling of transfer RNAs and their role as novel prognostic markers for breast cancer

Abstract: Transfer RNAs (tRNAs, key molecules in protein synthesis) have not been investigated as potential prognostic markers in breast cancer (BC), despite early findings of their dysregulation and diagnostic potential. We aim to comprehensively profile tRNAs from breast tissues and to evaluate their role as prognostic markers (Overall Survival, OS and Recurrence Free Survival, RFS). tRNAs were profiled from 11 normal breast and 104 breast tumor tissues using next generation sequencing. We adopted a Case-control (CC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 58 publications
1
42
0
2
Order By: Relevance
“…Using means of a new tRNA profiling method, investigators revealed that specific tRNAs, tRNA Arg CCG and tRNA Glu UUC , were upregulated in highly metastatic breast cancer cells compared to poorly metastatic counterpart due to their enhanced stability and translation of the codon-rich transcripts [ 57 ]. These up-regulated tRNAs might serve as potential novel prognostic markers in addition to their involvement in the pathogenesis of breast cancer [ 69 ].…”
Section: Trnas and Trna Derivatives In Breast Cancermentioning
confidence: 99%
“…Using means of a new tRNA profiling method, investigators revealed that specific tRNAs, tRNA Arg CCG and tRNA Glu UUC , were upregulated in highly metastatic breast cancer cells compared to poorly metastatic counterpart due to their enhanced stability and translation of the codon-rich transcripts [ 57 ]. These up-regulated tRNAs might serve as potential novel prognostic markers in addition to their involvement in the pathogenesis of breast cancer [ 69 ].…”
Section: Trnas and Trna Derivatives In Breast Cancermentioning
confidence: 99%
“…Danielson et al [71] and Umu et al [72] identified 356 and 411 unique tRNAs, respectively, in plasma using RNA sequencing approaches. It is estimated that cells express between 300 and 400 tRNA genes, based on microarray [73][74][75][76] or RNA sequencing approaches [31,[77][78][79]. This number is consistent with RNA polymerase III and TFIIIC occupancy [80][81][82].…”
Section: Discussionmentioning
confidence: 61%
“…piRNA transcripts were also observed to be generated from long noncoding RNAs which are >200 nt in length. In addition, we [ 118 , 119 ] and others [ 120 – 123 ] have suggested that transfer RNAs and small nucleolar RNAs may also be the sources of piRNAs as we observed some of the piRNA genes to exist within the boundaries of transfer RNAs and small nucleolar RNAs [ 118 – 123 ]. However, the process through which piRNA transcripts are generated remains elusive.…”
Section: Piwi-interacting Rnas (Pirnas)mentioning
confidence: 86%